African studies - Burtynsky, Edward 1955- (Steidl, 2022)
In Edward Burtynsky’s recent photographs, produced across the African continent, the patterns and scars of human-altered landscapes initially appear to form an abstract painterly language; they reference the sublime and often surreal qualities of human mark-making. While chronicling the major themes of terraforming and extraction, urbanization and deforestation, African Studies conveys the unsettling reality of sweeping resource depletion on both a human and industrial scale. From natural landscapes to artisanal mining and mechanized extraction, several distinct chapters culminate with China in Africa: a series depicting the economic inroads being made by China, including the interiors of gigantic newly built manufacturing plants. This project brings together the work of seven years, presenting the latest installment in Burtynsky’s ongoing uvre
Keywords: Burtynsky, Edward -- 1955-; Geschichte 2016-2019; Umweltschaden; Umweltverschmutzung; Fotografie; Rohstoffgewinnung; Industrialisierung; Luftbild; Afrika; Urbanisation; Entwaldung; Abholzung; Landschaft; Umwelt; Bildband